Product diversification in a small open economy. - Loh, Shyh. (2008)
This is a study on diversification strategy, specifically on the relationship between a firm's diversification strategy and its economic performance during the historic normal growth period of Singapore, in contrast to the period of the Asian Financial Crisis of 1997 and its aftermath.